Low ventilatory responsiveness to transient hypoxia or breath-holding predicts fast marathon performance in healthy middle-aged and older men - Bartłomiej Paleczny (Nature Portfolio, 2021)
Abstract The aim of this study was to test the utility of haemodynamic and autonomic variables (e.g. peripheral chemoreflex sensitivity [PCheS], blood pressure variability [BPV]) for the prediction of individual performance (marathon time and VO2max) in older men. The post-competition vasodilation and sympathetic vasomotor tone predict the marathon performance in younger men, but their prognostic relevance in older men remains unknown. The peripheral chemoreflex restrains exercise-induced vasodilation via sympathetically-mediated mechanism, what makes it a plausible candidate for the individual performance marker. 23 men aged ≥ 50 year competing in the Wroclaw Marathon underwent an evaluation of: resting haemodynamic parameters, PCheS with two methods: transient hypoxia and breath-holding test (BHT), cardiac barosensitivity, heart rate variability (HRV) and BPV, plasma renin and aldosterone, VO2max in a cardiopulmonary exercise test (CPET). All tests were conducted twice: before and after the race, except for transient hypoxia and CPET which were performed once, before the race. Fast marathon performance and high VO2max were correlated with: low ventilatory responsiveness to hypoxia (r =  − 0.53, r = 0.67, respectively) and pre-race BHT (r =  − 0.47, r = 0.51, respectively), (1) greater SD of beat-to-beat SBP (all p < 0.05). Fast performance was related with an enhanced pre-race vascular response to BHT (r =  − 0.59, p = 0.005). The variables found by other studies to predict the marathon performance in younger men: post-competition vasodilation, sympathetic vasomotor tone (LF-BPV) and HRV were not associated with the individual performance in our population. The results suggest that PCheS (ventilatory response) predicts individual performance (marathon time and VO2max) in men aged ≥ 50 yeat. Although cause-effect relationship including the role of peripheral chemoreceptors in restraining the post-competition vasodilation via the sympathetic vasoconstrictor outflow may be hypothesized to underline these findings, the lack of correlation between individual performance and both, the post-competition vasodilation and the sympathetic vasomotor tone argues against such explanation. Vascular responsiveness to breath-holding appears to be of certain value for predicting individual performance in this population, however.